CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM COMMUNITY BASED EMPOWERMENT (TO INCREASE THE PRODUCTIVITY OF MICRO, SMALL AND MEDIUM BUSINESS) IN GORONTALO DISTRICT - Luqmanu Hakiem Ajuna; Riya Andriyani Ahmad; Spandi Rauf; Moh. Akbar Ibrahim (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Business Development in Gorontalo District Creation of micro, small and medium enterprises is one of the poverty reduction strategies (MSMEs). MSMEs, on the other hand, have many challenges in Gorontalo District. The business world plays an active role in solving MSME problems in Gorontalo Regency through the CSR program. Based on the facts and problems above, this study provides a paradigm of community empowerment-based corporate social responsibility. 1) Examine the problems and demands faced by MSMEs in Gorontalo District. 2) make a CSR plan that emphasizes community empowerment. The approach used is observation and in-depth interviews with MSMEs in Gorontalo District. Based on the study, MSMEs in Gorontalo Regency are constrained by financial and marketing problems. Leading CSR programs include funding, education, and marketing (promotion) through MSME exhibitions and bazaars. Keywords: UMKM (Micro, Small and Medium Enterprises), Corporate Social Responsibility, Community Empowerment Productivity.